Magnetotelluric Image of Transcrustal Magmatic System Beneath the Tulu Moye Geothermal Prospect in the Ethiopian Rift - Friedemann Samrock; Alexander V. Grayver; Hjalmar Eysteinsson; Martin O. Saar (Geophysical Research Letters)
Abstract Continental rifting is initiated by a dynamic interplay between tectonic stretching and mantle upwelling. Decompression melting assists continental breakup through lithospheric weakening and enforces upflow of melt to the Earth's surface. However, the details about melt transport through the brittle crust and storage under narrow rift‐aligned magmatic segments remain largely unclear. Here we present a crustal‐scale electrical conductivity model for a magmatic segment in the Ethiopian Rift, derived from 3‐D phase tensor inversion of magnetotelluric data. Our subsurface model shows that melt migrates along preexisting weak structures and is stored in different concentrations on two major interconnected levels, facilitating the formation of a convective hydrothermal system. The obtained model of a transcrustal magmatic system offers new insights into rifting mechanisms, evolution of magma ascent, and prospective geothermal reservoirs.